Peculiarities of international investment in renewable energy (Economics and region, 2022)
The growth of renewable energy in recent years is due to the combination of private investment, government subsidies, and favourable regulatory frameworks. Renewable energy, particularly wind and solar, has emerged as a dominant player in the energy sector and continues to be the cheapest option for new electricity generation in many countries. The primary sources of financing are public funding, venture capital, and private equity. With the maturity of the renewable energy sector, the need for venture capital and private equity funding has declined. However, mergers and acquisitions play a critical role in financing renewable energy by enabling early investors to exit their investments and redeploy their capital. Solar photovoltaics receive the majority of renewable energy investments and spending. The European Union is at the forefront of renewable energy development, with governments and private investors recognising the importance of transitioning to clean energy sources for economic and environmental reasons. The shift towards renewable energy results in job creation and economic growth and improves energy security by reducing reliance on fossil fuels and increasing self-sufficiency. In the next few years, the renewable energy sector will likely see a rise in investments from various stakeholders. The private sector has a critical role in the transition to a low-carbon energy system, and the growth of renewable energy sources profoundly impacts the global economy. Renewable energy boost creates jobs, drives innovation and improves energy security, making it a critical component of sustainable development. Furthermore, renewable energy projects can also benefit local communities by improving energy access and creating economic opportunities, such as developing microgrids in rural areas. This can lead to improved living standards, especially in developing countries with limited access to electricity. Therefore, the continued growth and development of renewable energy remains a critical goal for many countries and regions. The renewable energy sector is expected to grow, providing new opportunities and benefits to society.
Keywords: renewable energy sources; investment; government subsidies; venture capital; private equity